Temporary Waqf in Indonesia: Legal Basis and Implementation Challenges - Dermawan, Diki; Harahap, Abd Rahman (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2024)
This research aims to analyze the concept and implementation of temporary waqf by Law Number 41 of 2004 and evaluate the experience of the Darul Waqf Al-Hadiy Foundation in managing such waqf. The research method used is qualitative with an Empirical Law type, involving data collection through interviews and observations and qualitative descriptive analysis of primary and secondary data. The research results indicate that based on Law Number 41 of 2004, temporary waqf is permitted and regulated. However, implementing temporary waqf at the Darul Waqf Al-Hadiy Foundation faces various challenges, including difficulties in creating sustainable programs, high rehabilitation costs, and administrative complexity. Although temporary waqf provides significant benefits for Islamic religious education and the welfare of the local community, its management requires better education and improved competency for nazhir. More effective and sustainable waqf management can be achieved if the nazir has adequate experience and capabilities